THE MOTIVATION OF ELDERLY PEOPLE PRACTICING PHYSICAL ACTIVITY FOR HEALTH PROMOTION (Fiep Bulletin - online, 2019)
The motivation in the elderly for the practice of physical activities has been growing more and more over the years,they are motivated by medical indication, friends or family; either for reasons of health or improvement in the quality of life due tothe pathologies that occur with the advancement of age. The research had as objective to investigate the motivation of elderlypracticing physical activity in health promotion. Is a quantitative research, the procedure method is the descriptive of the surveytype. The subjects investigated were elderly individuals aged 60 years and over, participants in the Active Life Project: PhysicalActivity, Health and Longevity of the Integrated Faculties of Patos – (FIP), in the city of Patos - PB. The Questionnaire is about theMotivation of Physical Activity Seniors (QMIPAF), constructed and validated by Lucena & Serpa (2013), and an interview to verifythe pathologies of the elderly were used as instrument. The questionnaire is composed of two distinct parts, the first of which aimsto know the sociodemographic and physical activity characteristics of the elderly, and the second to investigate the motivation ofelderly practicing physical activity in health promotion. The collected data were analyzed through the descriptive statistics of IBMSPSS statistics, version 21. The results of our study showed that the elderly investigated focused strongly on factors that aremotivated to practice physical activities to promote and improve their health in the search for a better quality of life for a SuccessfulOld Age.
Keywords: Motivation; Aging; Physical activity; Health